Book Review: HALL, CHRISTOPHER J., SMITH, PATRICK H., & WICAKSONO, RACHEL. Mapping Applied Linguistics: A Guide for Students and Practitioners. London, UK: Routledge. - Kartchava, Eva; McMonagle, Melissa; Romancio, Joshua (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2014)
HALL, CHRISTOPHER J., SMITH, PATRICK H., & WICAKSONO, RACHEL. Mapping Applied Linguistics: A Guide for Students and Practitioners. London, UK: Routledge (2011). 411 pp. $42.19 (paperback). (ISBN 978-0-415-55913-3).